DEVELOPMENT OF GASTRONOMIC TOURISM AS A TOURIST ATTRACTION DURING THE COVID-19 PANDEMIC IN THE EX-SURAKARTA RESIDENCY - Giyah Yuliari; Bambang Riyadi; Putra Perdana (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The development of a variety of culinary delights into gastronomic tourism can be a choice of tourist attractions. The uniqueness of gastronomic tourist attraction is built through acculturation, differentiation and modification. In its application, the Gastronomic Tourism Attraction is informed in the form of tour packages and disseminated through the website. The role of the website is very important, the manager of a travel agent must be able to choose a strong internet service provider, so that information can quickly reach tourists virtually, without being face-to-face so that it can break the chain of spreading Covid-19. The study was designed as a qualitative study with in-depth descriptive analysis. The research was conducted at Ex. Surakarta Residency, Central Java. Data analysis used qualitative and interpretative descriptive analysis. The results show that the gastronomic tourist attraction is an alternative tourist destination, which can be offered to tourists, without ignoring New Normal and Health Protocols.